2017
DOI: 10.1051/alr/2017019
|View full text |Cite
|
Sign up to set email alerts
|

Blue whiting (Micromesistius poutassou) sex ratio, size distribution and condition patterns off Portugal

Abstract: The sex ratio is an important trait of natural populations and a key parameter for assessing the reproductive potential and stock status of exploited fish populations. In fisheries research, knowledge on spatial and temporal sex ratio variation can inform on the capacity of a population to support exploitation and environmental changes. Blue whiting (Micromesistius poutassou) shows sexual growth dimorphism after maturation, with females achieving greater lengths than males. The main goal of this work was to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…This becomes apparent from 25 cm TL, when females were dominant in number. The size range found was similar to that previously observed in the Mediterranean (García et al, 1981;Macpherson and Duarte, 1991;Massutí et al, 2008;Serrat et al, 2019) and smaller than that reported for the Atlantic population (Gonçalves et al, 2017;Mahe et al, 2016). The minimum fished size, 3 cm TL, indicates that the recruitment to the demersal habitat takes place at smaller size than previously reported in the western Mediterranean, between 11.5 and 14 cm (Bas, 1964;García et al, 1981;Moranta et al, 2000) and similar to that mentioned in other Mediterranean areas (Ligurian , Northern Tyrrhenian and Ionian Seas) (D'Onghia et al, 2010;Mannini and Lanteri 2015;Viva et al 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This becomes apparent from 25 cm TL, when females were dominant in number. The size range found was similar to that previously observed in the Mediterranean (García et al, 1981;Macpherson and Duarte, 1991;Massutí et al, 2008;Serrat et al, 2019) and smaller than that reported for the Atlantic population (Gonçalves et al, 2017;Mahe et al, 2016). The minimum fished size, 3 cm TL, indicates that the recruitment to the demersal habitat takes place at smaller size than previously reported in the western Mediterranean, between 11.5 and 14 cm (Bas, 1964;García et al, 1981;Moranta et al, 2000) and similar to that mentioned in other Mediterranean areas (Ligurian , Northern Tyrrhenian and Ionian Seas) (D'Onghia et al, 2010;Mannini and Lanteri 2015;Viva et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Blue whiting, Micromesistius poutassou (Risso, 1827), is a pelagic gadoid widely distributed in the North Atlantic and the Mediterranean Sea, inhabiting over the shelf edge and continental slope (Bailey, 1982;Heino et al, 2008). There is large amount of information on its biology, behavior and fisheries for the Northeast Atlantic (Bailey and Heath, 2001;Bailey, 1982;Gonçalves et al, 2017;Hátún et al, 2009;Payne et al, 2012), but less is known for the species in the Mediterranean despite it has an important commercial interest, particularly in the northern part (Bas, 1963;Bas and Calderon-Aguilera, 1989;Martin et al, 2016;Orsi-Relini and Peirano 1985;Serrat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…; Gonçalves et al. ), and/or spatiotemporal sex‐segregation (Swain ; Gerritsen et al. ; Loher and Hobden ; Okamura et al.…”
mentioning
confidence: 99%
“…; Gonçalves et al. ; Haugen et al. ) may bias biological reference points and compromise the success of management strategies.…”
mentioning
confidence: 99%
“…Mackerel performs extensive annual migrations with distinct spawning, feeding, overwintering and nursery areas (Boyd et al, 2018;. Blue whiting performs seasonal and diel vertical migrations (Gonçalves et al, 2017). Herring also undergo extensive migrations between feeding and spawning grounds (Kotterba et al, 2017).…”
Section: Introductionmentioning
confidence: 99%